2021
DOI: 10.1021/acsami.1c05940
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Organic Film Stacks Containing Solution-Processed Phosphorescent Poly(dendrimer) Dopants

Abstract: Efficient organic light-emitting diodes (OLEDs) consist of an emissive layer comprising a blend of a light-emitting and host material in contact with one or more charge transporting layers. The distribution of the active material in the guest–host emissive layer blend and the changes that may occur upon thermal annealing are two important factors in determining the stability and efficiency of OLEDs. We have combined neutron reflectometry and photoluminescence measurements to investigate the structures of films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In particular, NR offered a quantitative evaluation of the composition of O-O interfaces in angstrom-ordered resolution and revealed that the onset temperature of thermal diffusion at O-O corresponds to the glass transition temperature (T g ) of the materials. [14][15][16][17] Based on such depth profile measurements, several studies asserted that the intermixing at the HTL/EML interface improved current injection or suppressed triplet polaron quenching and thereby enhanced the device performance. 11,14 However, those performance enhancements might predominantly be due to the thermally modified morphologies of organic layers rather than interface mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NR offered a quantitative evaluation of the composition of O-O interfaces in angstrom-ordered resolution and revealed that the onset temperature of thermal diffusion at O-O corresponds to the glass transition temperature (T g ) of the materials. [14][15][16][17] Based on such depth profile measurements, several studies asserted that the intermixing at the HTL/EML interface improved current injection or suppressed triplet polaron quenching and thereby enhanced the device performance. 11,14 However, those performance enhancements might predominantly be due to the thermally modified morphologies of organic layers rather than interface mixing.…”
Section: Introductionmentioning
confidence: 99%